PENGARUH KONVEKSI MOLEKUL TERHADAP DISTRIBUSI WAKTU TINGGAL - Putut Irwan Pudjiono (Jurnal Kimia Terapan Indonesia, 1995)
Residence Time Distribution studies were performed in a continuous vertical Couette Flow device under the conditions of negligible molecular diffusion. Most of the experiments were carried out in the laminar flow region. Diethylene glycol (DEC, 'Analar grade', BDH, Poole) were used as the flowing fluid. 1% Congo red dye solution in DEC was used as the tracer and it was injected as an impulse input through the injection port situated at the bottom of the device. The temperature was maintained at 20°C during the course of the experiments. The responses were analyzed using the mixing cup technique. The C-curves obtained were analyzed theoretically using the equation originally derived for flow through annulus. Such an approach was applied since both Couette and annular flow device have similar geometry. The responses of the secondary flow induced by the cylinder rotation at Tas>Tac were expected to be observed as the curve change from the curve characterizes the laminar flow through annulus to normal distribution.